Implikasi Hukum Pidana Terhadap Penyalahgunaan Dana Zakat Dalam Tindak Pidana Korupsi - Subihat, Ihat; Abdurrachman, Hamidah; Malik Mufty, Abdul (Faculty of Law, Universitas Pekalongan, 2025)
The misuse of zakat funds for criminal acts of corruption represents a significant challenge in Indonesia, a country with the largest Muslim population in the world. Zakat, as one of the pillars of Islam, plays a crucial role in wealth redistribution, poverty alleviation, and social justice. The research employs a normative juridical approach, utilizing library research and qualitative analysis to explore the legal framework, challenges in law enforcement, and the socio-economic impacts of zakat fund corruption.The findings reveal that misuse of zakat funds, through embezzlement, budget mark-ups, and program diversion, not only violates positive law but also contravenes Islamic sharia principles. The study highlights the detrimental effects of such corruption on public trust, social solidarity, and the economic empowerment of mustahik (zakat recipients). Furthermore, it underscores the long-term consequences, including increased poverty, social inequality, and hindered economic development.